Effects of emulsifier type and environmental stress on the stability of curcumin emulsion. Issue 10 (3rd October 2017) - Wu, Min-Hui; Yan, Hong Hai; Chen, Zhao-Qing; He, Mei
ABSTRACT: The objective of this study was to investigate the effects of environmental stress and emulsifier types on the stability of curcumin emulsions. Results showed that Lecithin and Tween 80 presented good emulsifying capacity. The Tween 80 emulsion was the most stable among the four emulsions. The particle sizes of Tween 80 and whey protein emulsion were relatively smaller than gum arabic and lecithin. Extensive droplet aggregation appeared in whey protein-stabilized emulsions when the pH was approximately isoelectric point (pI) with salt concentration >200 mM. Lecithin emulsion was unstable when pH ≤ 6 with salt concentration >100 mM. There was little impact of pH and ionic strength on gum arabic and Tween 80 emulsions. All of the emulsions were stable at temperatures from 30 to 90°C in the absence of salt. These results help characterize the emulsifying and stabilizing abilities of emulsifier types intended for applications in the food industry. GRAPHICAL ABSTRACT: